Training Basic Skills of Scientific Writing and Publication to Improve Research Competence - Yusuf, Muhammad; Pahala, Indra; Ulupui, I Gusti Ketut Agung; Muliasari, Indah; Marsellisa; Hasanah, Nuramalia; R, Tresno Eka Jaya; Sasmi, Aji Ahmadi; Zairin, Gentiga Muhammad (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
The purpose of community service is the achievement of the tri dharma of higher education by providing knowledge that can be applied by the community. This training aims to encourages the academic community to play an active role in research activities. By the theme of the event, this activity is also present to provide benefits in the form of education for both lecturers and students in preparing themselves to make a scientific journal. The Community Service Team held initial discussions with several lecturers from several universities that have cooperation with the Faculty of Economics, Jakarta State University such as YKPN Polytechnic University Yogyakarta, STABN Raden Wijaya Wonogiri, STIE Pertiwi, STIAB Jinarakkhita Lampung, Podomoro University, Dian Nusantara University, Gunung Swaadaya University. Teak. The partners discussed their desire to receive the Basic Skills Training for Scientific Writing and Publication to Improve Research Competence. The method used is qualitative with descriptive analysis techniques. This activity is carried out so that partners can have basic skills in writing scientific papers and publications in international journals. The result of training in writing articles and scientific publications is to improve the quality of research in universities that have an impact on society.